IMMUNOMODULATORY EFFECTS OF GARLIC AND TULSI IN REPEAT BREEDING CROSSBRED COWS - KUMAR, SUNIL; GUPTA, H P; PRASAD, SHIV; SINGH, BEERENDRA (The Indian Journal of Animal Reproduction, 2011)
Role of crude extracts of garlic and tulsi as an agent to stimulate uterine defense mechanism was studied byexamining total protein and immunoglobulins in uterine flushing of repeat breeding cows and compared with mostsensitive antibiotic (enrofloxacin), selected on the basis of antibiogram. Forty crossbred repeat breeding cowswith endometritis were selected on the basis of history, appearance of cervical mucus and white side test afterthorough per-rectal examination. Cows were divided randomly into five groups viz.A, B, C, D and E (control). 30 mlcrude extracts of garlic, tulsi, garlic+tulsi, diluted with distilled water (1 :5) were infused intrauterine, thrice, at 24hrs interval starting on day of estrum in cows of group A, B and C, respectively. Similarly, enrofloxacin, selected onthe basis of antibiO!Jram (30 ml} and PBS (30 ml) were infused in cows of group D and E, respectively. Uterineflushings were collected at O hrs ( day of estrum before treatment) and considered as "O" hour collection of uterine .flushing. Second uterine flushing was also collected at 72 hrs of first flushing. These flushings were used for·estimation of total protein and immunoglobulins. Results revealed a non significant rise in total protein after garlic,tulsi and garlic+tulsi treatment. On the other hand, there was significant increase (p
Keywords: Repeat breeding cows; Herbal extracts; lmmunomodulators